2003
DOI: 10.1366/000370203321558182
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Attenuated Total Reflection and Transmission Spectra Studied by Dispersion Analysis

Abstract: Fourier transform infrared transmission (FT-IR) and attenuated total reflection (ATR) spectra of water-ethanol mixtures are recorded and reconstructed thanks to a causal dispersion analysis technique. As expected, the Beer's law technique is an empirical approximate method that cannot account for complex spectral features. On the other hand, a rigorous analysis performed by using the theoretical optical paths for both experimental techniques and Gaussian dispersion analysis (GDA) allows the dielectric function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…4a . Qualitatively these spectra are globally similar to each other and to published ATR spectra of liquid water in the MIR region (e.g., MacDonald and Bureau 13 and Elderderi et al), 23 but to the author’s knowledge, none of the previously reported ATR spectra of water covered the far-infrared spectral region. The direct observation of the two spectra in Fig.…”
Section: Determination Of the Optical Functions Of Liquid Watersupporting
confidence: 86%
See 1 more Smart Citation
“…4a . Qualitatively these spectra are globally similar to each other and to published ATR spectra of liquid water in the MIR region (e.g., MacDonald and Bureau 13 and Elderderi et al), 23 but to the author’s knowledge, none of the previously reported ATR spectra of water covered the far-infrared spectral region. The direct observation of the two spectra in Fig.…”
Section: Determination Of the Optical Functions Of Liquid Watersupporting
confidence: 86%
“…[10][11][12] In what concerns ATR spectroscopy, a comprehensive fitting of the spectra using this same approach to extract the optical functions is seldom used. Examples of such an approach are the works of MacDonald and Bureau 13 and also Milosevic et al 14 The works of Piro et al, 15 Guida et al, 16 Balan et al, 17 and Aufort et al 18 partially follow that path by using dielectric dispersion models to simulate the ATR spectra, but the model parameters were computed from other spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, this method is referred to as FEWS for fiber evanescent wave spectroscopy, because it is assumed that the principle of the measurement is based on the presence of evanescent waves at the surface of the fiber, simultaneously with the propagation of light into the fiber. The theoretical aspect of FEWS measurements has already been discussed in previous papers [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%